ANALISIS KESULITAN BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS VI SDIT IQRO GEDONG TATAAN PESAWARAN - Asep Bambang Susanto; Usman (Program Studi Pendidikan Agama Islam, 2023)
Learning is a necessity for all living things, especially humans in living life. Through the process of learning to make changes in humans for the better. The sample in this study was all grade VI students of SDIT Iqro Gedong Tataan Pesawaran with a total of 25 students. Data collection techniques in this study are interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and data verification. Factors that affect the learning outcomes of Islamic religious education include: internal factors, external factors, method factors and factors of facilities and infrastructure